PENERAPAN MODEL KOOPERATIF TIPE STAD BERBANTUAN WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR IPA - Riska Ayu Pratiwi; Martini Martini (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
This study aims to describe the increase in student learning motivation after the implementation of the STAD type cooperative model assisted by interactive media (Wordwall). This type of research is a quantitative study with a One Group Pretest-Posttest design involving 29 students of class VII-C at SMP at Sidoarjo as research subjects. The learning motivation instrument is a learning motivation questionnaire containing 25 statements based on indicators developed by Sudibyo: choice of tasks, effort, persistence, and self-confidence. The instruments used include learning motivation questionnaire sheets (pretest and posttest). Data analysis techniques used paired t-test and N-Gain calculation. The results of the study showed that there was an increase in student learning motivation in the high category. All aspects of learning motivation experienced an increase, with the effort aspect showing the most significant increase with an N-gain score of 0.73. It can be concluded that the implementation of the STAD cooperative learning model assisted by Wordwall is effective in increasing student learning motivation in science learning.